Penyelesaian Klaim pada Asuransi Kendaraan Bermotor Melalui Badan Mediasi Asuransi (Lex Jurnalica, 2009)
Insurance or about responsibility is indentured among two parties or more by which underwriter party fasten self to the insureds by accept insurance premiums to give substitutions to been taken on because loss, damage or expected gain loss, or takes on jawah law to third party who may will suffer evoked the insured of a scene that not absolutely, or to give a payment that didasarka on dies or its life someone which be underwritten (section 1 sentence (1 ) UU No. No. Years 1992). In motor vehicle insurance agreement not close its happening possible dispute, that dispute usually in term claim which because of the insured party and also the insurer. One of the ways penyelesian that dispute is through Warm Up Mediasi Indonesia Insurance (BMAI). Mediasi's body Indonesia Insurance (BMAI) constitute an independent body that have mediator mediator what does commisioned independent to perform insurance claim dispute working out among reassured with underwriter. Insurance claim dispute is dispute among the insured with the insurer that reverential one of the parties not carry on deal already being made with every consideration or even because available party that wanprestasi, so disadvantages one of the parties. Dispute working out procedure motor vehicle insurance claim via 2 phases which is phase mediasi and ajudikasi's phases. If dispute gets most solve at mediasi's phase therefore finish dispute, on the contrary if dispute can't be solved at mediasi's phase therefore its working out is drawned out to ajudikasi's phase. Are not all claim dispute can thru solve Mediasi's Body Indonesia Insurance (BMAI) since exists requisite who shall be accomplished by the insured. Although that requisite were accomplished, are not close possible dispute working out process insurance claim via Warms Up Mediasi Indonesia Insurance (BMAI) will be constrained. Keywords: Claim, Insurance, Motor vehicle